The Use of Animated Drawing Applications as a Medium to Grow Self-Confidence in Elementary School Students' Character Drawing Abilities - Fauziah Wulansari; Markhamah Markhamah; Ambarwati Ambarwati (Journal of Educational Sciences, 2026)
The rapid development of digital technology has encouraged innovation in art education, particularly through interactive media that support students’ creative and psychological development. This study aims to examine the role of the Animated Drawing application in enhancing elementary school students’ self-confidence in drawing imaginative figures in fine arts learning. The research was conducted at UPTD SDN 1 Kepandean involving 41 fifth-grade students and employed a qualitative descriptive approach. Data were collected through participatory observation, in-depth interviews with students and teachers, and documentation of students’ drawings and animated works. Data validity was ensured through triangulation, while data analysis followed the interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate an improvement in students’ self-confidence after the use of the Animated Drawing application. Students showed greater willingness to display their artwork, increased pride in seeing their drawings transformed into animation, and higher enthusiasm during learning activities. The animation process reduced fear and embarrassment and encouraged freer expression of ideas. However, students’ confidence in communicating learning difficulties to teachers remained moderate. Overall, the study concludes that Animated Drawing effectively supports self-confidence and creative expression in elementary art education.